2018
DOI: 10.1111/jpn.13017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E supplementation on performance, serum biochemical parameters and fatty acid composition of egg yolk in laying hens fed a diet containing ageing corn

Abstract: This study investigated whether dietary vitamin E (VE) supplementation could alleviate any detrimental effects of ageing corn in the diet for laying hens on egg performance, egg quality, serum biochemical parameters, cholesterol content and the fatty acid (FA) profile of egg yolks. The experiment consisted of a 2 × 3 factorial design with two corn types (normal corn and ageing corn) and three concentrations of VE (0, 20 and 100 IU/kg). A total of 216 Lohmann laying hens (50‐week‐old) were randomly allocated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
4
10
0
Order By: Relevance
“…In contrast, Kaya & Turgut (2012) reported that supplementation of 150 mg/kg vitamin E increased egg production. However, similar to the results found in this study, Mu et al (2019) reported that supplementation of vitamin E did not affect egg production. b,c The difference between means with different superscript letters in the same row is significant (P <0.05)…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, Kaya & Turgut (2012) reported that supplementation of 150 mg/kg vitamin E increased egg production. However, similar to the results found in this study, Mu et al (2019) reported that supplementation of vitamin E did not affect egg production. b,c The difference between means with different superscript letters in the same row is significant (P <0.05)…”
Section: Resultssupporting
confidence: 91%
“…Niu et al (2018) reported that the efficacy of meat quality and antioxidant capacity in chickens fed with 200 mg/kg vitamin E diet was greater compared with those fed with 100 mg/kg vitamin E diet. Mu et al (2019) reported that average daily feed intake, egg weight and egg production rose with increasing dietary vitamin E supplementation. In addition, with the transfer of vitamin E from feed to egg, oxidative stability was increased, shelf life was prolonged, the fatty acid composition in the egg yolk was improved (Mohiti-Asli et al, 2008) and the oxidation of omega-3 fatty acids was inhibited (Arab-Tehrany et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, 100% ageing corn in a diet reduced the laying rate, feed intake, egg weight, antioxidant status of laying hens, albumen height, yolk colour and polyunsaturated fatty acid of eggs. Vitamin E supplementation were unable to counteract the adverse effects ( Mu et al., 2018 ; Zhou et al., 2019 ). Whether reducing the levels of ageing corn can alleviate the decreasing of antioxidant capacity of eggs and antioxidant status of laying hens are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Free fatty acids in maize are easily oxidized, producing lipid hydroperoxides, which affects catalase (CAT) and peroxidase (POD) activities [6]. The addition of dietary aged maize increases the amount of exogenous reactive oxygen species (ROS) and leads to lipid peroxidation, which may cause oxidative stress with negative impacts on animal health [7,8,9,10]. However, Mitchell and Beadles [11] reported that when maize was stored from 730 to 1020 d, there was no consistent or significant deterioration in the digestibility or the biological value of the maize when fed to rats.…”
Section: Introductionmentioning
confidence: 99%